Cadmium armors the Cd hyperaccumulator Sedum alfredii against aphid attack - Xu, Lingling; Lu, Lingli; Lin, Xianyong; Hu, Yan (Frontiers in Environmental Science, 2022)
The cadmium (Cd) hyperaccumulator Sedum alfredii has been identified to have great ability to accumulate >100 ppm (dry weight) of Cd in its aboveground biomass. However, little attention has been paid to the possibility that S. alfredii may benefit from this trait. Here, we investigated the effect of Cd accumulation on the performance of the black bean aphid Aphis fabae in S. alfredii. The results showed that 6 weeks of Cd exposure prevented S. alfredii from being infested by aphids. In another experiment, S. alfredii was pretreated with 100 μmol⋅dm⁻³ CdCl2 for 7 days. Prolonged Cd exposure significantly reduced the number of aphids in the Cd-pretreated S. alfredii after 7 days of aphid infestation. The Cd concentration in the phloem exudates of S. alfredii was also high. Micro X-ray fluorescence mapping of aphids collected from Cd-treated plants revealed high levels of Cd in the stylets. In summary, Cd protects S. alfredii from A. fabae through toxicity, but not deterrence, which may be related to the abundance of Cd in the phloem.